The role of unawareness, volition, and neural hyperconnectivity in alcohol use disorder: a functional magnetic resonance imaging study - Hornoiu, Iasmina; Lee, Alycia; Tan, Haoye; Nakovics, Helmut; Bach, Patrick; Mann, Karl; Kiefer, Falk; Sommer, Wolfgang H.; Vollstädt-Klein, Sabine (Biological psychiatry. Cognitive neuroscience and neuroimaging, 2023)
Background - Automated alcohol craving and habitual alcohol consumption characterize the later stages of alcohol use disorder (AUD). This study reanalyzed previously collected functional neuroimaging data in combination with the Craving Automated Scale for Alcohol (CAS-A) questionnaire to investigate the neural correlates and brain networks underlying automated drinking characterized by unawareness and nonvolition. - Methods - We assessed 49 abstinent male patients with AUD and 36 male healthy control participants during a functional magnetic resonance imaging-based alcohol cue-reactivity task. We performed whole-brain analyses examining the associations between CAS-A scores and other clinical instruments and neural activation patterns in the alcohol versus neutral contrast. Furthermore, we performed psychophysiological interaction analyses to assess the functional connectivity between predefined seed regions and other brain areas. - Results - In patients with AUD, higher CAS-A scores correlated with greater activation in dorsal striatal, pallidal, and prefrontal regions, including frontal white matter, and with lower activation in visual and motor processing regions. Between-group psychophysiological interaction analyses showed extensive connectivity between the seed regions inferior frontal gyrus and angular gyrus and several frontal, parietal, and temporal brain regions in AUD versus healthy control participants. - Conclusions - The present study applied a new lens to previously acquired alcohol cue-reactivity functional magnetic resonance imaging data by correlating neural activation patterns with clinical CAS-A scores to elucidate potential neural correlates of automated alcohol craving and habitual alcohol consumption. Our results support previous findings showing that alcohol addiction is associated with hyperactivation in habit-processing regions, with hypoactivation in areas mediating motor and attention processing, and with general hyperconnectivity.